Scrutinizing EFL Teachers’ Emotions in the Indonesian Context of Bandung - Alvian Adhi Nugroho; Concilianus Laos Mbato (Journal of English Education and Teaching, 2021)
This study aims to investigate the most dominant emotions experienced by EFL teachers in the Indonesian context. Two kinds of questionnaires were employed in this study. This research involved participants of Bandung English Teachers. They were 72 EFL teachers who participated on the general scale of phase 1 and 68 EFL teachers who joined the specific scale questionnaire of phase 2. Three dimensions of emotions were explored in this research to know the level of emotions faced by teachers. Also, positive and negative emotions have been explored in this paper. A quantitative descriptive method was used to examine the data from two questionnaires as the main research instrument. This study adapted the Teacher Emotion Scale invented by Frenzel et al. (2016). The descriptive findings show that from two studies enjoyment is the most frequently experienced and anger is the lowest dimension of emotion preferred by EFL teachers. This study has proven the reliability of the research instrument. The research analysis shows that there is an insignificant difference between the two studies and both of them have a very close resemblance.